1005 Tut2

Download as pdf or txt
Download as pdf or txt
You are on page 1of 4

MATH11005 — Tutorial 2

1. Solve the IVP: y 0 + y = x + ex , y(0) = 0.


Solution: 1) Find the integrating factor I(x)
R
1dx
I(x) = e = ex .

2) Multiply the original equation by I(x) we have

ex (y 0 + y) = ex (x + ex ), ⇒ (ex y)0 = xex + e2x .

3) Integrate the two sides:


Z
1 1
e y = [xex + e2x ]dx = xex − ex + e2x + C, ⇒ y = x − 1 + ex + Ce−x .
x
2 2

By y(0) = 0, c = 12 . Thus

1 1
y = x − 1 + ex + e−x .
2 2

2. Solve the following DE:


2 y3
y0 + y = 2 .
x x
Solution: This is a Bernoulli DE with n = 3.
1) Let u = y 1−n = y −2 . Then u0 = (1 − n)y −n y 0 = −2y −3 y 0 , ⇒ y 0 = − 21 y 3 u0 .
2) Substitute this into the DE we have

1 2 y3 1 2 1
− y 3 u0 + y = 2 , ⇒ − u0 + y −2 = 2 ,
2 x x 2 x x
1 2 1
⇒ − u0 + u = 2 , ⇒
2 x x
4 2
u0 − u = − 2 . (1)
x x
3) Now we have a linear DE.
R
− x4 dx 1
I(x) = e = e−4 ln |x| = .
x4

1
4) Multiply (1) by I(x):
1 0 4 2 1 1 2
4
(u − u) = − 2 4 ⇒ ( 4 u)0 = − 6 , i.e.,
x x x x x x
 u 0 2
4
= − 6.
x x
5) Integrating two sides we have
u 2 2 2
4
= 5 + C, ⇒ u = + Cx4 , ⇒ y −2 = + Cx4 .
x 5x 5x 5x
3. Solve the initial-value problem:

3x2 y 2 + 8xy 5 + (2x3 y + 20x2 y 4 )y 0 = 0, y(2) = 1.

Solution: Let P (x, y) = 3x2 y 2 + 8xy 5 , Q(x, y) = 2x3 y + 20x2 y 4 . Then Py =


6x2 y + 40xy 4 , Qx = 6x2 y + 40xy 4 . Py = Qx . The equation is exact.
There exists f (x, y) such that

fx (x, y) = P (x, y) = 3x2 y 2 + 8xy 5 , (1)

and
fy (x, y) = Q(x, y) = 2x3 y + 20x2 y 4 . (2)
Integrating (1) to x we have

f (x, y) = x3 y 2 + 4x2 y 5 + g(y). ⇒

fy (x, y) = 2x3 y + 20x2 y 4 + g 0 (y).


Combining this with (2) we have g 0 (y) = 0. ⇒ g(y) = C. ⇒

f (x, y) = x3 y 2 + 4x2 y 5 + C.

The solution is
x3 y 2 + 4x2 y 5 = C.
Sub y(2) = 1: C=24. Thus the solution is

x3 y 2 + 4x2 y 5 = 24.

2
4. Find an integrating factor y 5 + (2xy 4 − yey )y 0 = 0.

Solution: Here
∂P ∂Q
∂y
− ∂x 3
=
−P y
so that there is an integrating factor which is a function of y only, which satisfies
3
I 0 /I = ,
y

I(y) = y 3 .

5. Find an integrating factor and thus solve the equation:

1 − xy + x(y − x)y 0 = 0, x > 0.

Solution: Let P (x, y) = 1 − xy, Q(x, y) = x(y − x). Then Py = −x, Qx = y − 2x.
Py 6= Qx . The equation is not exact.
Note that
Py − Qx x−y 1
= =− .
Q x(y − x) x
We can find an integrating factor which is a function of x only.
Z  Z 
Py − Qx 1 1
I(x) = exp dx = exp − dx = .
Q x x
There exists a potential function f (x, y) such that
1
fx (x, y) = I(x)P (x, y) = − y, (1)
x
and
fy (x, y) = I(x)Q(x, y) = y − x. (2)
Integrating (1) to x we have
Z
1
f (x, y) = ( − y)dx + g(y) = ln x − xy + g(y). ⇒
x

fy (x, y) = −x + g 0 (y).

3
Combining this with (2) we have g 0 (y) = y. ⇒ g(y) = 21 y 2 . ⇒

1
f (x, y) = ln x − xy + y 2 + C.
2
The solution is
1
ln x − xy + y 2 = C.
2

6. Given that y1 (x) = ex is a solution of the DE y 00 − 3y 0 + 2y = 0. Find a second


linearly independent solution.
Solution:
Z Z Z
1 − R p(x) dx 1 − R −3 dx
u(x) = e dx = e dx = ex dx = ex .
y12 (ex )2
Z
y2 (x) = y1 (x) u(x) dx = e2x .

You might also like